2007
DOI: 10.1352/1934-9556(2007)45[380:lala]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness and Living Arrangements

Abstract: Adults with ID/DD live in increasingly small community settings, where the risk of loneliness may be greater. We examined self-reported loneliness among 1,002 individuals with ID/DD from 5 states in relation to community residence size, personal characteristics, social contact, and social climate. One third reported being lonely sometimes and one sixth said they were often lonely, but loneliness was not more common for people living alone or in very small settings. More loneliness was reported by residents of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 14 publications
2
48
1
Order By: Relevance
“…Some of these, such as vulnerability to exploitation, are similar to previous research about supported living (Emerson et al, 2001;Felce et al, 2008). Our findings are similar to other research that suggests loneliness is an enduring issue for people with intellectual disability (Sheppard-Jones, Thompson Prout, & Kleinert, 2005;Stancliffe et al, 2007). They do not reflect Stancliffe et al's(2007) finding that very small-sized living arrangements or social contacts may be associated with less loneliness.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Some of these, such as vulnerability to exploitation, are similar to previous research about supported living (Emerson et al, 2001;Felce et al, 2008). Our findings are similar to other research that suggests loneliness is an enduring issue for people with intellectual disability (Sheppard-Jones, Thompson Prout, & Kleinert, 2005;Stancliffe et al, 2007). They do not reflect Stancliffe et al's(2007) finding that very small-sized living arrangements or social contacts may be associated with less loneliness.…”
Section: Discussionsupporting
confidence: 87%
“…Stancliffe and Keane (2000) suggested that early studies in the US indicated that loneliness posed a particular concern for people in supported living, but their study found similar high levels of loneliness in group homes and supported living. However, Stancliffe et al's(2007) survey of 1,002 people with mild to moderate intellectual disability in the US found that although loneliness was an issue for half the sample, people living in very small settings (1-3 people) or who had more contact with family and friends reported less loneliness.…”
Section: Introductionmentioning
confidence: 99%
“…Controlling for individual characteristics and living environment variations, companion articles to the present study have reported greater choicemaking among HCBS recipients, and those living in smaller settings (Lakin et al, 2007) and more loneliness among residents of larger (7-15 residents) community settings (Stancliffe et al, 2007). Neither of these companion articles contrasted outcomes for those living with family members or not or for those who chose where and with whom to live or not.…”
contrasting
confidence: 46%
“…This suggests that loneliness requires sustained attention by service providers, policymakers, and researchers. We have examined the loneliness data in considerably more detail in a companion paper (Stancliffe et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The more individualised the support situation, the greater the opportunity for relationships with community members (Stancliffe et al, 2007). Policymakers can seek out funding streams and policies that promote smaller and more individualised residential supports.…”
Section: Promote Individualised Living Settings and Support For Relatmentioning
confidence: 99%